Research Note : Characterization and phylodynamic analysis of new infectious bursal disease virus variants circulating in Argentina - Jaton, Juan Marcelo; Lozano Calderon, Laura Camila; Gambini, Pablo; Ponti, Marina; Gomez, Evangelina Raquel; Konig, Guido Alberto; Chimeno Zoth, Silvina Andrea (Elsevier, 2024)
Infectious Bursal Disease is a highly contagious disease that affects young chickens and leads to significant economic losses. Its causal agent is a double-stranded RNA virus that, due to its high error rate during the replication process, gives rise to a constant generation of new virus variants. Until 2014, strains of Infectious Bursal Diseases Virus (IBDV) belonging to genogroup 4 predominated in Argentina, but there have been no reports since then regarding the circulating genogroups in poultry. In this study, 11 recent sequences of Argentine from the hypervariable region of VP2 protein (hvVP2) were analyzed to determine their genogroup, origin, evolution, and amino acid sequence. Samples from chickens showing signs of IBDV infection were collected, and the hvVP2 region was amplified using RT-PCR, followed by sequencing. The results indicated that the analyzed strains belong to genogroup 2, with an estimated evolutionary rate of 1.74 × 10−3 substitutions/site/year. It is speculated that the predominant group of sequences began to spread in Argentina around 2014 and had its origins in China. Another sample is related to strains from South Korea and is not closely linked to the main group. Furthermore, the predicted amino acid sequences show similarity to strains that can evade vaccine-induced immunity. These findings underscore the importance of active surveillance in poultry to mitigate losses caused by IBDV.